PELATIHAN PEMBUATAN RAMUAN OBAT TRADISIONAL DENGAN MEMANFAATKAN KUNYIT DAN DAUN KETAPANG PADA MASYARAKAT KAMPUNG CABANG 2 KELURAHAN AMBAN - Enik Maturahmah; Revisika Revisika; Wiska Baharuddin (LP4MK STKIP PGRI Lubuklinggau, 2022)
Medicinal plants are all species of medicinal plants that are known and believed to have efficacy as traditional medicine so that they can be used as self-medication efforts. Kampung Branch 2, kel Amban is one of the villages located in Kab. Manokwari, West Papua. The majority of the villagers have large yards and gardens because the villagers are generally farmers. Around their environment there are many ketapang trees and around the community yard many turmeric plants have not been used optimally. The purpose of this activity is to provide information to the community, especially the residents of Kampung Branch 2, kel. Amban, about various kinds of medicinal plants and how to use medicinal plants, especially in ketapang leaves and turmeric, to cure various kinds of minor ailments, as well as how to use them and the right dosage. The method used in this activity is to use lectures that are educating the participants consisting of several villagers and provide hands-on practical training together. The results of the service showed that there was an increase in the knowledge of the people of the Branch 2 village, Amban village who were present at the service activity about training in making traditional medicinal herbs using turmeric and ketapang leaves in the community of branch 2 village, Amban village. This can be seen from the ability of the participants during the discussion to be able to answer or provide explanations when the implementing team asks questions.